Analysis of the Investment Environment and Influencer Factors - ugli, Ochilov Bobur Bakhtiyor (PT. Riset Press International, 2025)
This article covers the classification of investments, the analysis of factors affecting investment attractiveness, and the impact of foreign investments on developing the country's economy. It presents foreign and domestic scientists' scientific and theoretical views on the topic. It also presents the essence and theoretical foundations of attracting foreign investments in the development of the national economy and formulates scientific conclusions and recommendations on improving the investment climate.